1999
DOI: 10.1161/01.hyp.34.4.889
|View full text |Cite
|
Sign up to set email alerts
|

The Aging Process Modifies the Distensibility of Elastic but not Muscular Arteries

Abstract: Abstract-Aging decreases the distensibility of large elastic arteries; however, the effects of age on the functional parameters of muscular, medium-sized arteries are not well determined. This study evaluated the consequences of aging on the functional parameters of the carotid and radial arteries in normotensive men. A total of 62 elderly subjects (aged 74Ϯ2 years) were compared with 87 young subjects (aged 35Ϯ3 years). Internal diameter and intima-media thickness (IMT) were measured by a high-resolution echo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
59
2
9

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 23 publications
5
59
2
9
Order By: Relevance
“…According to Langewouters (35), C A of the aged human thoracic aorta at 100 mmHg is about one-third of that of the mid-aged aorta. The compliance of large human conduit arteries at operating pressure decreases with age, according to several other reports in the literature (11,20,30,42,44,51,61). D A of the human aorta also decreases with age at operating pressure.…”
Section: Discussionsupporting
confidence: 55%
“…According to Langewouters (35), C A of the aged human thoracic aorta at 100 mmHg is about one-third of that of the mid-aged aorta. The compliance of large human conduit arteries at operating pressure decreases with age, according to several other reports in the literature (11,20,30,42,44,51,61). D A of the human aorta also decreases with age at operating pressure.…”
Section: Discussionsupporting
confidence: 55%
“…It is also known that the aging process modifies the distensibility of carotid arteries. 46 Ebrahim et al 47 also reported the relation between IMT of common carotid artery and risk factors of stroke and stroke prevalence. Cupini What is known about this topic K The Third National and Nutrition Evaluation Survey showed that during middle age, men had higher blood pressure than women.…”
Section: Discussionmentioning
confidence: 98%
“…19 The accuracy of the system is 30 m for the diastolic diameter measurement and Ͻ1 m for the pulsatile change in diameter (difference between systolic and diastolic diameters). 20 All of the measurements were performed on the right common carotid arteries 1 cm below the bifurcation at the site of the distal wall, as assigned in other studies using the same methodology. 19,20 …”
Section: Vascular Parametersmentioning
confidence: 99%
“…20 All of the measurements were performed on the right common carotid arteries 1 cm below the bifurcation at the site of the distal wall, as assigned in other studies using the same methodology. 19,20 …”
Section: Vascular Parametersmentioning
confidence: 99%